Case Report: Long-Term Chemotherapy With Hydroxyurea and Prednisolone in a Cat With a Meningioma: Correlation of FDG Uptake and Tumor Grade Assessed by Histopathology and Expression of Ki-67 and p53 - Yun, Taesik; Koo, Yoonhoi; Kim, Hakhyun; Lee, Wonguk; Kim, Soochong; Jung, Dong-In; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2021)
A 15.5-year-old, neutered, male, domestic shorthair cat was presented with neurologic dysfunctions. At presentation, an obtunded mental status and vestibular ataxia were identified. On neurologic examination, postural reactions were decreased-to-absent in all four limbs, and pupillary light reflexes showed bilaterally delayed results. Magnetic resonance imaging was performed, and a demarcated lesion was identified in the third ventricle. The cat was tentatively diagnosed with a brain tumor, which was suspected to be a meningioma. The cat was treated with hydroxyurea and prednisolone. Mental status was considered more alert, and ataxia improved following treatment. On the 106th day after the commencement of treatment, a 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) scan was performed. On the PET images, a hypermetabolic region was found in the lesion. The average standardized uptake value of FDG was 2.47, and the tumor-to-normal-tissue ratio was 1.25. The cat died 408 days following the commencement of treatment, and a grade 1 meningioma was confirmed by postmortem histopathology. Immunohistochemistry for Ki-67 and p53 was performed. The labeling indices of Ki-67 and p53 were 2.56 and 0%, respectively. This case shows that chemotherapy with hydroxyurea and prednisolone may be considered in the treatment of feline meningiomas. Furthermore, this is the first case describing the application of FDG-PET to visualize a naturally occurring meningioma in a cat.